Chrononutrition and circadian disruption as modulators of diet-induced obesity: when you eat may matter as much as what you eat - Amin Roshdy Soliman (The Egyptian Journal of Internal Medicine, 2026)
Abstract The obesity epidemic has been framed predominantly through energy balance and diet composition, with less attention to the temporal dimension of food intake. Emerging evidence indicates that meal timing and circadian disruption independently modulate susceptibility to diet-induced obesity. Peripheral clocks in the liver, adipose tissue, pancreas, and skeletal muscle are entrained by food intake independently of the light-entrained central clock, and eating during the biological night promotes central–peripheral desynchrony at a time of reduced insulin sensitivity and fatty acid oxidation. Epidemiological and interventional studies link social jetlag, shift work, artificial light at night, delayed eating, and late dinners to higher adiposity and impaired glycemic and lipid outcomes. Chronotype further modifies risk, and emerging data suggest that genetic variation in core clock genes may partly explain interindividual differences in metabolic responses to meal timing. We propose a chrono-obesogenic framework in which the metabolic impact of dietary exposures is modulated by temporal alignment with the circadian system. Advancing this framework requires standardized chrononutrition terminology, trials crossing diet composition with meal timing, chronotype- and genotype-aware analyses, and integration of light exposure into obesity prevention strategies. Meal timing deserves standing alongside diet quantity and quality in both clinical counselling and obesity research.